Analysis of Factors and Conditions Influencing Military Neurosurgery Recruitment and Retention. (20th December 2019) - Menger, Richard; LeFever, Devon C; Zuckerman, Scott L; Robbins, J Will; Bell, Randy
Abstract: Introduction: The Defense Health Agency has shifted focus of military medicine to operational readiness. As such, neurosurgery remains a critical wartime specialty. We investigate the factors impacting recruitment and retention of military neurosurgeons. Methods: Survey of military neurosurgeons was performed via the American Association of Neurological Surgeons/Congress of Neurological Surgeons Joint Committee of Military Neurosurgeons and the Council of State Neurosurgical Societies. Retention and recruitment were queried. Results: 93/119 (78.2%) current or previously affiliated military neurosurgeons would recommend service as a military neurosurgeon to a colleague. Those who felt a sense of patriotism were 4.3 times more likely to recommend military service ( P = 0.027, CI 1.19–16.82). Those who developed a sense of camaraderie showed a trend to recommending military neurosurgery ( P = 0.058, CI 0.95–9.78). Those with a current military obligation were.28 times ( P = 0.02, CI 0.09–0.85) as likely to recommend service. Military physicians who felt a need for reform to increase salary were 2.5 times less likely to be retained. Discussion: Service in the US military is a positive experience with camaraderie, patriotism, and unique military experiences predictive of recruitment. Meanwhile, focus on pay discrepancy can result in lost retention. These factors should be explored regarding recruitment and retention of military neurosurgeons.